Deep sequence analysis of HIV adaptation following vertical transmission reveals the impact of immune pressure on the evolution of HIV. - Jennifer Currenti; Abha Chopra; Mina John; Shay Leary; Elizabeth McKinnon; Eric Alves; Mark Pilkinton; Rita Smith; Louise Barnett; Wyatt J McDonnell; Michaela Lucas; Francine Noel; et al. (PLoS Pathogens)
Human immunodeficiency virus (HIV) can adapt to an individual's T cell immune response via genomic mutations that affect antigen recognition and impact disease outcome. These viral adaptations are specific to the host's human leucocyte antigen (HLA) alleles, as these molecules determine which peptides are presented to T cells. As HLA molecules are highly polymorphic at the population level, horizontal transmission events are most commonly between HLA-mismatched donor/recipient pairs, representing new immune selection environments for the transmitted virus. In this study, we utilised a deep sequencing approach to determine the HIV quasispecies in 26 mother-to-child transmission pairs where the potential for founder viruses to be pre-adapted is high due to the pairs being haplo-identical at HLA loci. This scenario allowed the assessment of specific HIV adaptations following transmission in either a non-selective immune environment, due to recipient HLA mismatched to original selecting HLA, or a selective immune environment, mediated by matched donor/recipient HLA. We show that the pattern of reversion or fixation of HIV adaptations following transmission provides insight into the replicative cost, and likely compensatory networks, associated with specific adaptations in vivo. Furthermore, although transmitted viruses were commonly heavily pre-adapted to the child's HLA genotype, we found evidence of de novo post-transmission adaptation, representing new epitopes targeted by the child's T cell response. High-resolution analysis of HIV adaptation is relevant when considering vaccine and cure strategies for individuals exposed to adapted viruses via transmission or reactivated from reservoirs.